Left Ventricular Noncompaction in a Child with Turner Syndrome - Snigdha Bhatia; Amna Qasim; Murad Almasri; Luba Frank; Ashraf M. Aly (Case Reports in Pediatrics)
Congenital heart disease (CHD) may cause a significant comorbidity in patients with Turner syndrome. The commonly reported CHD in these patients includes bicuspid aortic valve and coarctation of the aorta. Left ventricular noncompaction (LVNC) is a rare form of cardiomyopathy that has been reported in literature only three times in adult patients with Turner syndrome. We report the first case of a 6-year-old asymptomatic female with Turner syndrome who was referred for cardiac evaluation after her Turner syndrome diagnosis. Echocardiogram was suspicious for LVNC, which was confirmed on cardiac magnetic resonance imaging.